A Self-report Oriented Toward Visuoperceptive and Visuomotor Alterations for the Early Identification of Dyslexic Children - , Carlo Aleci; , Claudio Rosa (Archives of Current Research International, 2020)
Background: Early diagnosis is the main requisite for rehabilitating children suspected to suffer from dyslexia, and self-reports may be as reliable as ordinary screenings, but far less expensive. Research shows that the visual function can be involved in the pathogenesis of dyslexia so that self-reports should inquire about visual signs as well. A questionnaire made of 21 items that provide scores based on the visual signs commonly reported by dyslexics and on the most relevant comorbidities according to the literature has been devised. The aim of this exploratory study is to evaluate its potential for the early identification of dyslexic children. Methods: The AAP-DD is a set of 21 items subdivided into 4 sections that inquire about visual signs (section S), fatty acid deficiency, inheritance of dyslexia, and related conditions in children and parents. Each item is assigned a specific visuomotor and visuosensory weight in the form of a coefficient. The parents of twenty-three dyslexic children (9.34±0.80 years) and twenty-four normal readers filled the questionnaire. To assess the correspondence between the outcome of the questionnaire and the actual visual function of each participant, spatial relationship perception and ocular movements have been tested psychophysically. Results: The score of the dyslexic sample was almost double (i.e. worse) compared to the control group (P <.0001). Sensitivity and specificity were, respectively, 87% and 62%. Section S was the most informative, accounting for up to 41% of the variance of the reading rate. Correlation between the DEM and the AAP-DD scores suggests the questionnaire reflects the actual visuomotor condition of the subject. Conclusion: The AAP-DD seems promising to screen children at risk for dyslexia, and is, therefore, worth to be further investigated in a larger population. The obtained results support the role of the visual function in the pathogenesis of this condition.